Pengaruh Latihan Multiball Terhadap Keterampilan Smash Forehand Tenis Meja Pada Club Pade Angen Mataram Tahun 2020 - Nurdin Nurdin; Aminullah Aminullah (Lembaga Penelitian dan Pendidikan Mandala, 2020)
The focus of the problem in this study is that this research is motivated by the low accuracy of the forehand smash. Table tennis at Club Pade Angen Mataram in 2020. The research objectives to be achieved based on the predetermined problem formulation are as follows: To find out the effect of multiball training on the smash forehand table tennis skills at Club Pade Angen Mataram in 2020. The research design in use is an experimental research